Development of Antigens in Human Cells Infected with Simian Virus 40 - Bissett, Marjorie L. (1966)
Bissett, Marjorie L. (University of Michigan, Ann Arbor), and Francis E. Payne. Development of antigens in human cells infected with simian virus 40. J. Bacteriol. 91:743–749. 1966.—An explanation for the apparent infrequency with which human cells transform in response to exposure to simian virus 40 (SV40) was sought by following the development of virus-induced antigens in human euploid cells, strain CR. For about 8 weeks after exposure to a high multiplicity of SV40, only a small proportion of the cells produced tumor (T) or viral (V) antigen detected by immunofluorescence. Double-tracer staining techniques revealed that the development of T and V antigen in about 1% of the CR cells resembled that in green monkey kidney cells, strain BS-C-1, in which SV40 replicates and destroys all the cells. T antigen was detected before V antigen; both antigens were detected in the nucleus, but only V antigen appeared later in the cytoplasm. All intact cells that contained V antigen also contained T antigen. Infected CR cell cultures, before and after transformation or when in “crisis,” contained only 0.1 to 1.0% of cells with both V and T antigen. Some CR cells contained only T antigen, and by 8 days after exposure to virus these cells were present as loose foci associated with an occasional cell containing V antigen. The proportion of CR cells with only T antigen increased from about 1% during the first 4 weeks to 8% at 7 weeks, and to nearly 100% at 11 weeks, when essentially all of the cells were epithelioid. Foci of epithelioid cells were first recognized in the 9th week. It was concluded that those CR cells that contained T antigen at any given time represented (i) a few cells that subsequently produced V antigen and lysed, and (ii) a progressively increasing population that produced only T antigen. If the latter population, in whole or in part, gave rise to the epithelioid transformed cells, then its initial size could account, at least in part, for the apparent infrequency with which human cells transform in response to SV40.